THE ROLE OF DISCOURSE MARKERS IN COMMUNICATION (Journal of Universal Science Research, 2025)
This thesis explores the linguistic and pragmatic functions of discourse markers in communication. It focuses on how elements such as ‘well, so, you know, and’ help speakers construct meaning, manage turns, express politeness and maintain coherence in various discourse situations. Using theories in pragmatics, discourse analysis and cognitive linguistics, the research investigates how these markers reflect cultural norms, social roles and conversational strategies across contexts.